CRIMINOLOGY: ACTUAL ISSUE FOR HIGHER EDUCATION IN UKRAINE - Лихова, Софія Яківна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Review of the textbook by Ivan Bogatyrev "Criminology". It is noted that the publication is one of today's fundamental types of work, the content of which the author reflects common problems of crime, characterized offender, described the causes and conditions of committing criminal offenses in society, and formulated measures to prevent crime in general and its individual manifestations. It was concluded that prepared a textbook on discipline "Criminology" meets the existing requirements for this type of work and can be recommended to students, cadets, students of higher education institutions, practices, law enforcement and the court to direct towards their creative independent work in the search for problem solving on prevention of crime in Ukraine.